Answer:
The answer is B.
Step-by-step explanation:
The original graph of y = x^2 has a vertex at (0,0)
The formula for graph translations is y = (x-#)^2+#
The number inside the parentheses is a horizontal translation.
So, we are given y = (x-(-3))^2+#
The vertex of the graph moves 3 points left, since the number is negative (-3).
The number at the end of the equation is a vertical translation.
So, we are given y = (x+3)^2+4
The vertex of the graph moves 4 points up, since the number is positive (4).
The new vertex is at (-3,4)